Is preclinical diabetic retinopathy in diabetic nephropathy individuals more severe? - Yao, Hongyan; Li, Zijing (Frontiers in Endocrinology, 2023)
Purpose: To analyse the retinal vessel density and thickness characteristics of diabetic nephropathy (DN) individuals with preclinical diabetic retinopathy (DR) using optical coherence tomography angiography (OCTA). Methods: This retrospective case‒control study included 88 eyes of 88 type 2 DM patients with preclinical DR [44 non-DN (NDN) and 44 DN]. OCTA images and data were acquired using AngioVue 2.0 of the spectral domain OCT device. The foveal avascular zone (FAZ) area, superficial capillary plexus (SCP) and deep capillary plexus vessel densities, ganglion cell complex (GCC) and full retinal thicknesses, peripapillary capillary density and nerve fibre layer (RNFL) thickness were compared between the NDN and DN groups. The relationship between each renal function parameter and each OCTA parameter was analysed. Results: SCP vessel density, GCC thickness and full retinal thickness were significantly reduced in DN individuals compared to NDN individuals [(NDN versus DN) SCP vessel density: 46.65±3.84% versus 44.35±5.25%, p=0.030; GCC thickness: 100.79±5.92 μm versus 93.28±8.66 μm, p<0.001; full retinal thickness: whole area: 287.04±13.62 μm versus 277.71±15.10 μm, p=0.005). Within the peripapillary area, capillary density was also significantly reduced in the whole area (50.19±3.10% versus 47.46±5.93%, p=0.016) and some sectors in the DN group, though RNFL thickness was only decreased in some sectors. For all individuals, estimated glomerular filtration rate (eGFR) correlated significantly with most OCTA parameters and then showed a significantly negative correlation with FAZ area (β=−16.43, p=0.039) in multivariate linear regression analysis. In the NDN group, eGFR showed a significantly negative correlation with FAZ area (β=−18.746, p=0.048) and a significantly positive correlation with SCP vessel density (β=0.580, p=0.036). Conclusion: Preclinical DR may be more severe in DN individuals than in NDN individuals with regard to microvascular and microstructural impairment. Moreover, eGFR may be a good indicator for retinal microvascular impairment.